1990
DOI: 10.1007/bf00422728
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of Aspergillus flavus in presence of Aspergillus niger during biosynthesis of aflatoxin B1

Abstract: Aspergillus niger or Aspergillus tamarii when grown as mixed cultures with toxigenic A. flavus inhibits biosynthesis of aflatoxin by A. flavus, owing primarily to its ability to produce inhibitors of aflatoxin biosynthesis and to their ability to degrade aflatoxin. Gluconic acid partly prevents aflatoxin production. The other factors such as changes in pH of the medium and the effect on the growth of a. flavus have no role in imparting capabilities to these cultures to inhibit aflatoxin production by A. flavus. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“… Horn and Wicklow (1983) indicated that A. niger lowered substrate to acidic pH value to suppress AFB 1 formation. Shantha et al (1990) demonstrated that oxalic acid and gluconic acid secreted by A. niger could prevent AFB 1 production ( Shantha and Rati, 1990 ; Shantha et al, 1990 ). However, some recent researches indicated that an antifungal peptide (AFP) isolated from A. niger could inhibit the growth of A. flavus and AFB 1 biosynthesis ( Lee et al, 1999 ; Xu et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“… Horn and Wicklow (1983) indicated that A. niger lowered substrate to acidic pH value to suppress AFB 1 formation. Shantha et al (1990) demonstrated that oxalic acid and gluconic acid secreted by A. niger could prevent AFB 1 production ( Shantha and Rati, 1990 ; Shantha et al, 1990 ). However, some recent researches indicated that an antifungal peptide (AFP) isolated from A. niger could inhibit the growth of A. flavus and AFB 1 biosynthesis ( Lee et al, 1999 ; Xu et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to various investigators who reported that a number of micro-organisms including bacteria, yeast and moulds, affected the production of aflatoxin in a competitive environment. Aspergillus niger when grown as mixed culture with toxigenic A. flavus inhibits biosynthesis of aflatoxin, owing primarily to its ability to produce inhibitors of aflatoxin biosynthesis and to degrade aflatoxin (Shantha et al 1990). According to Horn and Wicklow (1983), A. niger lowered substrate pH sufficiently and suppressed aflatoxin production.…”
Section: Discussionmentioning
confidence: 99%
“…The three strains were aggressive inhibitors of A. flavus growth, and macroscopic observations of mixed cultures showed highly predominant sporulating of A. niger, whereas AFB 1 was not detected. One strain led to a 90 % inhibition (C mean =1.9 µg mL -1 ) and another in 80 % inhibition (C mean =3.7 µg mL -1 ), primarily due to the action of gluconic acid, which is produced by A. niger (21)(22)(23).…”
Section: Resultsmentioning
confidence: 99%